2019
DOI: 10.1103/physrevb.99.115301
|View full text |Cite
|
Sign up to set email alerts
|

Interface effects on the magnetic-proximity-induced quantized Hall response in heterostructures based on three-dimensional topological insulators

Abstract: We report a theoretical study of the spin-dependent transport properties in heterostructures containing a three-dimensional topological insulator (TI) thin film and ferromagnetic normal insulator (FMNI) slab. Within the framework of a continual approach for the FMNI/TI/FMNI trilayer model, we reveal how the magnetic proximity effect at the TI/FMNI interface can influence an intrinsic Hall response of the system. We predict that the FMNI/TI/FMNI trilayer undergoes a transition into the quantum anomalous Hall ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Theoretical studies have shown that when a TI is sandwiched between two FMI, it can undergo a transition into the quantum anomalous Hall phase either from the topologically trivial phase or from the quantum spin Hall phase as a function of film thickness and strength of magnetic exchange. [ 212 ] Hou et al. have discussed the realization of QAHE at high temperature through DFT calculations for a van der Waals ferromagnet monolayer—CrI 3 interfaced with Bi 2 Se 3 , [ 42 ] and more detailed calculations predicted that when a Bi 2 Se 3 film with thickness of 5 QL or more is sandwiched between two CrI 3 layers, it becomes a QAHI due to the competition between the exchange field from CrI 3 and interaction of the top and bottom surfaces of Bi 2 Se 3 film.…”
Section: Recent Results In Topological Insulator (Ti) – Magnetic Materials (Mm) Heterostructuresmentioning
confidence: 99%
“…Theoretical studies have shown that when a TI is sandwiched between two FMI, it can undergo a transition into the quantum anomalous Hall phase either from the topologically trivial phase or from the quantum spin Hall phase as a function of film thickness and strength of magnetic exchange. [ 212 ] Hou et al. have discussed the realization of QAHE at high temperature through DFT calculations for a van der Waals ferromagnet monolayer—CrI 3 interfaced with Bi 2 Se 3 , [ 42 ] and more detailed calculations predicted that when a Bi 2 Se 3 film with thickness of 5 QL or more is sandwiched between two CrI 3 layers, it becomes a QAHI due to the competition between the exchange field from CrI 3 and interaction of the top and bottom surfaces of Bi 2 Se 3 film.…”
Section: Recent Results In Topological Insulator (Ti) – Magnetic Materials (Mm) Heterostructuresmentioning
confidence: 99%
“…However, our data does not show evidence of such an intercalation. Other interfacial effects, including charge transfer at the TI/MI interface and band bending could explain the absence of induced magnetism in the TI and the lack of observation of the QAHE [51][52][53][54][55]. Another possibility for the absence of proximity effects would be the presence of a magnetic dead layer at the TI/EuS interface.…”
mentioning
confidence: 99%
“…The disagreement between some spectroscopic probes indicating a relatively large exchange gap at the TI surface and the low temperature range of the QAHE realization remains an important matter [68]. The quantized conductivity effects in real systems are affected by a complex network of topologically non-trivial and trivial conducting channels running along boundaries, separating regions of distinct topological phases [69]. Our results demonstrate the presence of the DW-induced states embodying the conducting channels at the magnetic surface of TI and describe their characteristics.…”
Section: Discussion and Summarymentioning
confidence: 99%